Religious Message in Yusuf Estesâ€™ Public Lecture The Universal Messages of Islam (A Study of Politeness Strategies) - WA ODE AFIFAH CAHYANI (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2017)
Abstract This study aims to analyze politeness strategies and find out the religious message in Yusuf Estes' public lecture The Universal Message of Islam by using Brown and Levinson's theory. Brown and Levinson classified four strategies of politeness strategies namely; positive politeness, negative politeness, off record, and bald on record. This study used the descriptive qualitative method. The data for this study were taken from utterances of Yusuf Estes in his public lecture â€œthe universal message of Islamâ€. The data were collected from searching for the audiovisual of Yusuf Estesâ€™ public lecture, downloading, watching, reading, classifying, selecting, and coding the data. Then, the religious message contained in the expression of Yusuf Estes can increase knowledge as well as a reminder about the life of a servant based on the Qur'an and Sunnah. Then, the religious message contained in the expression of Yusuf Estes can increase knowledge so that it leads the servant to live based on the Qur'an and Sunnah. Keywords: public lecture, politeness strategies, religious message